2020
DOI: 10.1038/s41598-020-61950-y
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Endogenous Type I TGF-β Receptor Baboon in the Drosophila Brain

Abstract: the transforming growth factor β (tGf-β) signaling pathway is evolutionarily conserved and widely used in the animal kingdom to regulate diverse developmental processes. prior studies have shown that Baboon (Babo), a Drosophila type i tGf-β receptor, plays essential roles in brain development and neural circuit formation. However, the expression pattern for Babo in the developing brain has not been previously reported. We generated a knock-in fly with a human influenza hemagglutinin (HA) tag at the C-terminus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated miR-277 play various functional roles in flies, including circadian rhythm (Anna et al 2023), life span (Esslinger et al 2013), neurodegeneration and neuromuscular control (Tan et al 2012; Deshpante et al 2024; Cerro-Herreros et al 2016), homeostasis (Jones et al 2013; Li et al 2020), fatty acid metabolism (Zipper et al 2022), and amino acid metabolism (Esslinger et al 2013; Stark et al 2003). On the other hand, miR-34 has also been shown to play other roles in flies such as in autophagy, brain development, life span, survivorship, and regulation of ecdysone (Liu et al 2012, Lai et al 2016, Kennerdell et al 2018, McNeill et al 2020; Kennerdell et al 2018, McNeill et al 2020, Srinivasan et al 2022; Lai et al 2020; Xiong et al 2016). Together with the correlated expression data (AstC-R1, Kr-h1, miR-277 and miR-34), in vivo mutants construction, hormone measurement and transcriptomic analyses, this study strongly demonstrated that miR-277 and miR-34 can play cooperative biological roles in sesquiterpenoid hormones in the fly sexes during metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated miR-277 play various functional roles in flies, including circadian rhythm (Anna et al 2023), life span (Esslinger et al 2013), neurodegeneration and neuromuscular control (Tan et al 2012; Deshpante et al 2024; Cerro-Herreros et al 2016), homeostasis (Jones et al 2013; Li et al 2020), fatty acid metabolism (Zipper et al 2022), and amino acid metabolism (Esslinger et al 2013; Stark et al 2003). On the other hand, miR-34 has also been shown to play other roles in flies such as in autophagy, brain development, life span, survivorship, and regulation of ecdysone (Liu et al 2012, Lai et al 2016, Kennerdell et al 2018, McNeill et al 2020; Kennerdell et al 2018, McNeill et al 2020, Srinivasan et al 2022; Lai et al 2020; Xiong et al 2016). Together with the correlated expression data (AstC-R1, Kr-h1, miR-277 and miR-34), in vivo mutants construction, hormone measurement and transcriptomic analyses, this study strongly demonstrated that miR-277 and miR-34 can play cooperative biological roles in sesquiterpenoid hormones in the fly sexes during metamorphosis.…”
Section: Discussionmentioning
confidence: 99%